Influence Of Cooperative Learning Model Types Teams Games Tournament Quizizz's Help On Cognitive Science Learning Outcomes Of Junior High School Students - Ventiana, Yolanda Asri; Wedi, Agus; Fadhli, Muhibuddin (Proceedings Series of Educational Studies, 2024)
Type cooperative learning model Teams Games Tournament (TGT) is a learning model that involves the activities of all students and contains elements of play in small groups without any differences in status. Integration between types of cooperative learning models Teams Games Tournament (TGT) with Quizizz will make the learning process more fun and focused according to the stages of the learning model. This research aims to determine the effect of implementing a type of cooperative learning model Teams Games Tournament (TGT) assisted by Quizizz on the cognitive learning outcomes of junior high school students in science on vibration and wave material. This research design uses post-test only control group design with the type of research quasy experimental design. The research results show that the cooperative learning model is type Teams Games Tournament (TGT) has a significant influence on the cognitive science learning outcomes of junior high school students with a significance value (Sig.(2-tailed)) 0,000 < 0,005. Keywords: Cooperative Learning Model type Teams Games Tournament (TGT), Quizizz, Student Cognitive Learning Outcomes